Characterization of phenotypic range in DYRK1A haploinsufficiency syndrome using standardized behavioral measures. Issue 7 (14th March 2022) - Fenster, Rebecca; Ziegler, Alban; Kentros, Catherine; Geltzeiler, Alexa; Green Snyder, LeeAnne; Brooks, Elizabeth; Chung, Wendy K.
Abstract: DYRK1A haploinsufficiency syndrome is a well‐established neurodevelopmental disorder, but detailed information on the range of cognitive and behavioral issues associated with the condition is limited. We studied 24 participants with likely pathogenic or pathogenic variants in DYRK1A through the Simons Searchlight study and systematically assessed their medical history and development using standardized instruments: Vineland Adaptive Behavior Scale II (VABS‐II) and Child Behavior Checklists/1.5‐5 and 6‐18 (CBCL/1.5‐5, CBCL/6‐18). All of the individuals in the cohort had neurological manifestations including intellectual disability or developmental delay, microcephaly, autism spectrum disorder, and/or seizures. The severity of the neurodevelopmental disorder was variable with a few children scoring in the moderately low range on the adaptive behavior composite score on the VABS‐II. This study confirms the association of DYRK1A haploinsufficiency with neurodevelopmental disabilities, microcephaly, autism spectrum disorder, and epilepsy and quantifies the range of adaptive behaviors.